2004
DOI: 10.1159/000081339
|View full text |Cite
|
Sign up to set email alerts
|

Acute Interstitial Pneumopathy Associated with Docetaxel Hypersensitivity

Abstract: Background: Acute pulmonary toxicity in cancer patients treated with docetaxel has been reported in previous phase II studies and case reports. Unlike transient pulmonary infiltrates, it is demonstrated that docetaxel-induced interstitial pneumopathy is a severe clinical condition that generally leads to respiratory failure. Case Report: We report a patient with breast cancer who received 2 cycles of docetaxel in 3-week intervals and developed respiratory failure. The clinical, pathologic, and radiographic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The docetaxel-induced lung toxicity in the cases that have been reported usually occurred after the second to fourth course of chemotherapy, and was usually relieved with corticosteroid therapy. Therefore, the involvement of a cytotoxic T-cell-mediated mechanism is very likely [1,2,4,8,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The docetaxel-induced lung toxicity in the cases that have been reported usually occurred after the second to fourth course of chemotherapy, and was usually relieved with corticosteroid therapy. Therefore, the involvement of a cytotoxic T-cell-mediated mechanism is very likely [1,2,4,8,15].…”
Section: Discussionmentioning
confidence: 99%
“…Initially the symptoms may be non-specific. There may be cough, fever, acute bronchiolitis, dyspnoea initially on exertion then at rest, or sudden dyspnoea as in non-cardiogenic pulmonary oedema [3,15]. Respiratory failure may develop, being at times lethal [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary toxicities including acute bilateral infiltrates have been rarely reported, with a prevalence of grade 3 or more severe chronic fibrosing interstitial lung disease of approximately 0.7% [2]. Docetaxel has also been incriminated as a cause of severe chronic fibrosing interstitial lung disease that may lead to respiratory failure [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of taxane-induced pneumonitis or interstitial pneumonitis reported a risk of 3.8% in cases of esophageal cancer 5 and 1% to 9% in cases involving other malignancies, [6][7][8][9][10][11][12][13] some of which result in death. 10,[14][15][16][17][18][19][20][21] Moreover, anticancer agents may cause radiation recall, which is an uncommon and unpredictable phenomenon characterized by an acute inflammatory reaction confined to previously irradiated areas that is triggered by the administration of precipitating systemic agents, such as anticancer agents, some antibiotics, antituberculosis drugs, and the cholesterol-lowering medication simvastatin. [22][23][24][25][26] Taxane may evoke radiation recall pneumonitis with previous exposure to radiation therapy (RT), according to the drug package inserts (Taxotere; Sanofi, Tokyo, Japan; and Taxol; Bristol Myers Squibb, Tokyo, Japan).…”
mentioning
confidence: 99%